The Challenges to Indian IT Off-shoring Industry at the time of Global Economic Recession: An Insider’s View - Franklin, J.M.; Sivaprakasam, Dr. P.; Manivel, Dr. S. (Journal of Contemporary Research in Management (JCRM), 2013)
The global economy is nose diving to the bottom leading to be the worst financial crisis during the postwar period. (IMF) International Monetary Fund stated that growth was projected to slow appreciably. The world growth was projected to slow down from 5 percent in 2007 to 3.75 percent in 2008 and to just over 2 percent in 2009, with the downturn led by advanced economies. The activity in the advanced economies was expected to contract by 25 percent on an annual basis in 2009. The projections forecast have come true and the U.S. economy is suffering severely; the growth in Europe is hard hit and the growth out of exports in Japan has declined. These have collectively led to global economic crisis. The IT sector is the most affected industry. Currently 50% offshore business in India comes from US. Consequently, this is widely and deeply affecting the Indian Off-shoring industry. This paper presents comprehensively the challenges confronted by the Indian Off-shoring industry and the measures to be taken by the industry, associated institutions and the government.